Potential impact of mepolizumab in stepping down anti-osteporotic treatment in corticosteroid-dependent asthma - Domingo, Christian; Sogo, Ana; Casado, Enrique; Martínez-Moragón, Eva; Blanco-Aparicio, Marina; Carrillo, Teresa; Bañas-Conejero, David; Sánchez-Herrero, María-Guadalupe (Frontiers in Pharmacology, 2023)
Oral corticosteroids (OCS) are commonly used for the acute management of severe asthma exacerbations or as maintenance therapy; however, chronic use is associated with significant toxicities, e.g., osteoporosis. In the REal worlD Effectiveness and Safety (REDES) study of mepolizumab in a multicentric Spanish cohort of asthma patients, mepolizumab effectively reduced clinically severe asthma exacerbations and decreased OCS dependence. This post-hoc analysis further evaluates mepolizumab’s de-escalation effect on OCS dose. Patients enrolled in REDES who had OCS consumption data available for 12 months pre- and post-mepolizumab treatment were included in this analysis. Primary outcomes were to determine the change in the proportion of patients eligible for anti-osteoporotic treatment due to the changes in OCS consumption before and after 1 year of mepolizumab treatment. All analyses are descriptive. Approximately one-third (98/318; 30.8%) of patients in REDES were on maintenance OCS at the time of mepolizumab treatment initiation. In REDES, mean cumulative OCS exposure decreased by 54.3% after 1 year of treatment. The proportion of patients on high-dose OCS (≥7.5 mg/day) fell from 57.1% at baseline to 28.9% after 12 months of mepolizumab treatment. Thus, 53.6% of OCS-dependent asthma patients treated with mepolizumab would cease to be candidates for anti-osteoporotic treatment according to guidelines thresholds.